Construction of an endogenously activated catalytic DNA circuit for highly robust in vivo microRNA imaging. (August 2022) - Shang, Yu; Chen, Yingying; Wang, Qing; He, Yuqiu; He, Shizhen; Yu, Shanshan; Liu, Xiaoqing; Wang, Fuan
Abstract: Catalytic DNA circuit, a versatile synthetic molecular nanodevice, shows great potential for in vivo bioimaging application, yet is distorted by its off-site signal leakage. The endogenously activated DNA circuit could guarantee the specific and sensitive in vivo imaging utility yet was still unexplored. In this work, we engineered an endogenously and sequentially activated DNA circuit by using the specific enzymatic regulation strategy. This smart DNA circuit is consisting of two successive reaction modules, the initial site-specific circuitry exposure module and the subsequent circuitry activation module for amplified in vivo biosensing. Initially, the catalytic circuitry reactant was caged with a long elongated duplex, encoding with high energy barriers of circuitry crosstalk, to prevent the undesirable off-target signal leakage prior to its arrival in targeting cells. Subsequently, the as-integrated functional duplex could be specifically cleaved and removed by the endogenously overexpressed DNA excision repairing enzyme of cancer cells, thus liberating the DNA circuitry reactant for participating the catalyzed and amplified imaging of intracellular analyte, e.g., microRNA. Meanwhile, the catalytic DNA circuit stayed inert in normal cells for lacking the indispensable cell-specific exposure of circuitry reactant. Through the sequential circuitry exposure (by endogenous enzyme of specific cells) and activation (by target of interest) procedure, our multiply guaranteed DNA circuit realized the robust in vivo imaging of tumor cells with high precision and reliability, thus supplementing a powerful toolbox for cancer diagnosis and treatment. Graphical Abstract: An endogenously activated catalytic DNA circuit was engineered, through a cell-specific enzymatic modulation activation methodology, to achieve highly robust microRNA imaging in vivo . ga1 Highlights: An endogenously activated DNA circuit enables the intracellular imaging of miRNA through the enzyme-modulated methodology. This system acquires the high-contrast imaging of miRNA in live mice by preventing the annoying off-site signal leakage. The enzyme-regulation of DNA circuit facilitates the efficient and site-specific circuitry activation in specific live cells. This work provided a simple yet powerful strategy to regulate various DNA circuits with biologically important functions.